Stabilization of the amplitude of klystron modulator output pulses at 100 Hz PRR - Drugakov, A.N.; Leontjev, V.N.; Peplov, V.V. (Вопросы атомной науки и техники, 1999)
The accelerator timing system of the MMF has been upgraded. The new circuit produces more stable reference signals for the operating of the HV pulsed klystron modulator of the high-energy part of the linac. The stability of the output voltage from pulse to pulse at 100 Hz PRR provides the required stability of the klystron output RF power and accelerating field in cavities.